Enhanced chaotic image encryption algorithm based on Baker's map - Salleh, Mazleena; Ibrahim, Subariah; lsnin, Fauz (2003)
Performances in computer speed, media storage and network bandwidth. Along with this advancement, the fundamental issue of image security has become a major concern and because of this reason, research in image confidentiality has gained popularity amongst security experts. This paper discusses an alternative chaotic image encryption based on Baker’s map. This enhanced symmetric-key algorithm can support a variable-size image as opposed to the algorithm which is mainly based on Baker’s map that requires only square image for encryption. In addition, the algorithm also includes other functions such as password binding and pixel shifting to further strengthen the security of the cipher image. The algorithm also supports two modes of operation namely EBC and CBC. The number of iterations to be performed can vary depending on the security level required by the user. The paper also includes an example of image encryption. From the analysis done, it shows that the security level is high even though keys that are found to be weak keys for Baker’s map algorithm are being used in the algorithm.